Pyrrolo[1,2-a]quinoxalinic Core-Derived Compounds Targeting the Mycobacterium tuberculosis P-type ATPase Plasma Membrane Ca2+ Transporter, CtpF, as Potential Antituberculous Drugs - Michael Daniela Rodriguez-Afanado; Fabian Lopez-Vallejo; Cristian Ochoa-Puentes; Luz M. Salazar; Carlos Yesid Soto (International Journal of Mycobacteriology)
Background: The resistance of Mycobacterium tuberculosis (Mtb) on first- and second-line anti-tuberculosis (TB) drugs is an issue for TB control; therefore, developing new anti-TB drugs is a priority in TB research. In this sense, the Ca2+ P-type ATPase plasma membrane transporter CtpF is an interesting anti-TB drug target. Methods: In this work, the activity of 4C-substituted pyrrolo[1,2-a]quinoxalinic compounds on Mtb viability and Ca2+ ATPase activity mediated by the plasma membrane transporter, CtpF, was assessed. The pyrrolo[1,2-a]quinoxalines compounds were initially in silico and analyzed as potential inhibitors of the CtpF transporter. Molecular docking analyses showed that 4-(3,4-methylenedioxyphenyl) pyrrolo[1,2-a]quinoxaline (4b) and 4-(2-chlorophenyl) pyrrolo[1,2-a]quinoxaline (4c) compounds are potential CtpF inhibitors. These compounds were synthesized by green chemistry using deep eutectic solvent under environmentally friendly processes. Results: Even though both compounds, 4b and 4c, inhibit the plasma membrane Ca2+ ATPase activity mediated by the CtpF transporter (IC50 of 8.05 ± 0.04 µM and 9.15 ± 0.03 µM for 4b and 4c, respectively), only the 4b compound was active on Mtb cells (MIC = 25 µg/mL). Interestingly, compound 4b also showed low toxicity on VERO cells (19.65 ± 0.51%) and hemolytic activity (1.45 ± 0.20%) in human O Rh (+) erythrocytes. Conclusions: 4-(3,4-methylenedioxyphenyl) pyrrolo[1,2-a]quinoxalinic core-derived compounds could be useful for developing alternative anti-TB compounds.